Revision of the species of Mythimna Ochsenheimer, 1816 (Pseudaletia)(Lepidoptera: Noctuidae: Noctuinae: Leucaniini) occurring in Brazil - Madruga, Janaína (2022)
The genus Mythimna Ochsenheimer, 1816 groups aproximatelly 270 species worldwide. This genus is subdivided into many subgenera and species-groups, with those species occurring in the Neotropical region included in the subgenus Mythimna (Pseudaletia) Franclemont, 1951. Species of this subgenus frequently reach high population levels, causing economic damage to Poaceae cultivars. Hence, it is crucial a well-defined taxonomy allowing rapid and precise identifications. However, the species of this subgenus are cryptic, their recognition requires molecular analyses and in-depth morphological studies, which has often resulted in misidentifications. In Brazil, the occurrence of the following species had been mentioned: Mythimna (P.) adultera (Schaus, 1894), Mythimna (P.) roraimae Franclemont, 1951, Mythimna (P.) sequax Franclemont, 1951, and Mythimna (P.) unipuncta (Haworth, 1809). Yet, until now, we lack a broader knowledge about the geographic distribution and taxonomy of these species. Thus, this study aims to revise the taxonomy of those species based on morphological and molecular (COI) data to provide an updated comprehension of this group in the country. The analysis of 1,664 specimens allowed us to confirm the presence of three species in the country: Mythimna (P.) adultera, Mythimna (P.) sequax, and Mythimna (P.) unipuncta. A lectotype for Mythimna (P.) adultera is designated; a new synonym is proposed: Pseudaletia roraimae syn. nov. of Mythimna (P.) unipuncta; and a new species, Mythimna (P.) celiae sp. nov. is described from Bagé, Rio Grande do Sul, Brazil.